Flavonoids from the Flower Extract of Tecoma stans - Srivastava, B.K.; Reddy, M.V.R.K. (Asian Journal of Chemistry, 2010)
Systematic chemical investigation of the flower extract of Tecoma stans gave two new dihydroflavonols-3,4´,7-trihydroxy dihydroflavonol and 3,4´,5,7-tertrahydroxy-3´,5´-dimethoxy dihydroflavonol along with isorhamnetin. The structure elueidation was carried out by spectral analysis, colour reactions and degradation studies.